Water Quality Monitoring Using of Wireless Sensor - Singh Rawat, Bhupendra; Phulwari, Gaurav; Narayan Pandey, Trimurti (International Journal of Computer Sciences and Engineering, 2025)
The quality of water resources has a direct impact on the daily life of mankind and the sustainable development of society. However, with the rapid development of national industrialization, the current industrial wastewater discharge and improper handling have become more and more serious, especially for the growing domestic water pollution today; it is an urgent need for an efficient water quality monitoring system. With the rapid development of wireless sensor network application technology, people put forward higher requirements for the quality of water environment; wireless sensor network can be used in water environment for real-time monitoring of water quality.